In vivo effect of fluoride combined with amoxicillin on enamel development in rats (Journal of Applied Oral Science, 2022)
Some evidence in vitro suggested that amoxicillin and fluoride could disturb the enamel mineralization. Objective: To assess the effect of amoxicillin and of the combination of amoxicillin and fluoride on enamel mineralization in rats. Methodology: In total, 40 rats were randomly assigned to four groups: control group (CG); amoxicillin group (AG - amoxicillin (500 mg/kg/day), fluoride group (FG - fluoridated water (100 ppm -221 mg F/L), and amoxicillin + fluoride group (AFG). After 60 days, the samples were collected from plasma and tibiae and analyzed for fluoride (F) concentration. The incisors were also collected to determine the severity of fluorosis using the Dental Fluorosis by Image Analysis (DFIA) software, concentration of F, measurements of enamel thickness, and hardness. The data were analyzed by ANOVA, Tukey’s post-hoc test, or Games-Howell post-hoc test (α=0.05). Results: Enamel thickness of the incisors did not differ statistically among the groups (p=0.228). Groups exposed to fluoride (AFG and FG) have higher F concentrations in plasma, bone and teeth than those not exposed to fluoride (CG and AG). The groups showed a similar behavior in the DFIA and hardness test, with the FG and AFG groups showing more severe fluorosis defects and significant lower hardness when compared with the AG and CG groups, with no difference from each other. Conclusion: The rats exposed to fluoride or fluoride + amoxicillin developed dental fluorosis, while exposure to amoxicillin alone did not lead to enamel defects.